Ethanol acts on KCNK13 potassium channels in the ventral tegmental area to increase firing rate and modulate binge–like drinking. (January 2019) - You, Chang; Savarese, Antonia; Vandegrift, Bertha J.; He, Donghong; Pandey, Subhash C.; Lasek, Amy W.; Brodie, Mark S.
Abstract: Alcohol excitation of the ventral tegmental area (VTA) is important in neurobiological processes related to the development of alcoholism. The ionotropic receptors on VTA neurons that mediate ethanol-induced excitation have not been identified. Quinidine blocks ethanol excitation of VTA neurons, and blockade of two-pore potassium channels is among the actions of quinidine. Therefore two-pore potassium channels in the VTA may be potential targets for the action of ethanol. Here, we explored whether ethanol activation of VTA neurons is mediated by the two-pore potassium channel KCNK13. Extracellular recordings of the response of VTA neurons to ethanol were performed in combination with knockdown of Kcnk13 using a short hairpin RNA (shRNA) in C57BL/6 J mice. Real-time PCR and immunohistochemistry were used to examine expression of this channel in the VTA. Finally, the role of KCNK13 in binge-like drinking was examined in the drinking in the dark test after knockdown of the channel. Kcnk13 expression in the VTA was increased by acute ethanol exposure. Ethanol-induced excitation of VTA neurons was selectively reduced by shRNA targeting Kcnk13 . Importantly, knockdown of Kcnk13 in the VTA resulted in increased alcohol drinking. These results are consistent with the idea that ethanol stimulates VTA neurons at least in part by inhibiting KCNK13, a specific two-pore potassium channel, and that KCNK13 can control both VTA neuronal activity and binge drinking. KCNK13 is a novel alcohol-sensitive molecular target and may be amenable to the development of pharmacotherapies for alcoholism treatment. Graphical abstract: Image 1 Highlights: The ventral tegmental area (VTA) is important in neurobiological processes related to the development of alcoholism. Pharmacological evidence implicated two-pore potassium channels in ethanol-induced excitation of VTA neurons. Downregulation of KCNK13 (THIK-1) using shRNA decreased ethanol-induced neuronal excitation and increased binge-like drinking. KCNK13 may be an important target of ethanol in the VTA and other central nervous system regions.